Pathways for Holliday Junction Processing during Homologous Recombination in Saccharomyces cerevisiae - Ashton, Thomas M.; Mankouri, Hocine W.; Heidenblut, Anna; McHugh, Peter J.; Hickson, Ian D. (Molecular and Cellular Biology, 2011)
Article Usage Stats Services MCB Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue Spotlights in the Current Issue MCB About MCB Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy MCB RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0270-7306 Online ISSN: 1098-5549 Copyright © 2014 by the American Society for Microbiology. For an alternate route to MCB .asm.org, visit: MCB